Stillbirth rates in 20 countries of Latin America: an ecological study - Pingray, María Verónica (2018)
Objective: To describe country-level stillbirth rates and their change over time in Latin America, and to measure the association of stillbirth rates with socio-economic and health coverage indicators in the region. Design: Ecological study. Setting: 20 countries of Latin America. Population or Sample: Aggregated data from pregnant women with countries as units of analysis. Methods: We used stillbirth estimates, and socio-economic and healthcare coverage indicators reported from 2006 to 2016 from UNICEF, United Nations Development Programme and World Bank datasets. We calculated Spearman's correlation coefficients between stillbirths rates and socioeconomic and health coverage indicators. Main outcome measures: National estimates of stillbirth rates in each country. Results: The estimated stillbirth rate for Latin America for 2015 was 8.1 per 1000 births (range 3.1–24.9). Seven Latin America countries had rates higher than 10 stillbirths per 1000 births. The average annual reduction rate for the region was 2% (range 0.1–3.8%), with the majority of Latin America countries ranging between 1.5 and 2.5%. National stillbirth rates were correlated to: women's schooling (rS = −0.7910), gross domestic product per capita (rS = −0.8226), fertility rate (rS = 0.6055), urban population (rS = −0.6316), and deliveries at health facilities (rS = −0.6454). Conclusions: Country-level estimated stillbirth rates in Latin America varied widely in 2015. The trend and magnitude of reduction in stillbirth rates between 2000 and 2015 was similar to the world average. Socio-economic and health coverage indicators were correlated to stillbirth rates in Latin America. Tweetable abstract: Stillbirth rates decreased in Latin America but remain relatively high, with wide variations among countries.